New Attorney Bar Admission Ceremony at Valdez Hall Wine Room - Watkins, Howard::::::::: (1987)
Appellate Court administrator Vicki Hernandez administering the attorney oath to new admittees Front and side view of new attorneys; Ann Kinzel in tan and white top, Houry DerSimonian in gray suit/white blouse; Carol Corey in white jacket/2 black buttons